Analysis of the functional performance of the shoulder in swimming athletes with and without a history of injury - Soares, Isabela Cristina; Gonçalves da Silva, Maria Vitória; Toshiyuki Kumazawa, Matheus; Nahomi Kuroda, Melissa; Rodrigues Pedroni, Cristiane (Manual Therapy, Posturology & Rehabilitation Journal, 2023)
Background: Swimmers have a significant potential for shoulder injuries due to the unique nature of the different styles involved in swimming, as well as the high volume of repetitions required during training, which arise through repetitive strain and microtrauma. Injuries are the most frequent due to the repetitive use of the upper limb in overhead movements and factors related to Range of Motion (ROM) and strength. Objective: To analyze the performance of the shoulder of swimming athletes and to verify if there is a difference between athletes with and without a history of injury, as well as to verify the transmission between the performance of this joint with ROM and strength values. Methods: 24 competitive swimmers were evaluated, with an average age of 20 years (± 7.9). The glenohumeral internal rotation deficit (GIRD) and internal and external rotation ROM of the shoulder were evaluated using goniometry. Shoulder functionality was assessed using the closed kinetic chain test for upper limbs (CKCUEST). Handgrip strength was also evaluated with a dynamometer. SPSS software, version 21.0, was used and data were analyzed using Pearson's collaboration test and Student's t test for independent samples. Results: Athletes with a history of injuries had a higher weekly training load, although they did not differ in terms of the number of years practicing the sport. The performance in the CKCUEST was higher in the group without a history of injury (p=0.04) and there was no difference between the groups regarding the variables of total ROM and GIRD, as well as for grip strength. There was change only between the CKCUEST power values with the grip strength (p<0.05, r=0.677). Conclusion: The functional performance of the shoulder is greater in athletes without a history of injury.